Strategies and implications of mitigating personnel shortages in nursing homes - Dörte Heger; Annika Herr; Maximilian Lückemann; Arndt R. Reichert; Leonie Tycher (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Amidst demographic shifts, advanced economies are facing critical nursing shortages. This study analyzes strategies of German nursing care providers to address these shortages using administrative data for the period 2007 to 2017. Our analysis reveals that higher nursing shortages correlate with decreased nurseto-resident ratios, changes in the qualification mix of nurse personnel, and reduced care provision. These findings suggest that nurse shortages can be a threat to the quality of care and the financial sustainability of nursing homes at the margin of being profitable. – – Aufgrund des demografischen Wandels sind viele Länder mit einem gravierenden Mangel an Pflegekräften konfrontiert. Diese Studie analysiert Strategien deutscher Pflegeheimbetreiber zur Bewältigung des Personalmangels anhand administrativer Daten für den Zeitraum von 2007 bis 2017. Unsere Analyse zeigt, dass ein höherer Personalmangel mit einem geringeren Pflegekräfte-Bewohner/in-Verhältnis, Veränderungen im Qualifikationsmix des Pflegepersonals sowie einem reduzierten Pflegeangebot korreliert. Diese Ergebnisse deuten darauf hin, dass der Mangel an Pflegekräften die Qualität der Pflege und die finanzielle Nachhaltigkeit von Pflegeheimen gefährden kann.
Keywords: C90; I10; I11; I18; J01; 330; Nursing home care; personnel shortage; capacity; nursing management